Quality of care and user satisfaction in a Health Center in Ancash, Peru - Mosqueira-Cueva, Edgar Dino (2025)
One of the functions of public health management is to evaluate the quality of care and user satisfaction in order to identify deficient areas, reduce obstacles that affect primary care, and improve the user experience, with the aim of building a system that fosters trust and increases satisfaction. Therefore, this study aimed to determine the relationship between Quality of Care (QC) and User Satisfaction (US) in a health center in Áncash, Peru. It employed a quantitative approach, of a basic type, with a non-experimental, cross-sectional design and a descriptive-correlational level. A total of 131 users were surveyed using two questionnaires. Statistical analysis yielded a p-value < .05, evidencing a statistically significant relationship, and a Spearman’s Rho = .741, which revealed a strong positive correlation. The study concluded that quality of care and its dimensions are correlated with user satisfaction; as quality of care improves in the health center studied, user satisfaction tends to increase, and vice versa.